Program Kampus Mengajar Dalam Meningkatkan Literasi dan Numerasi Peserta Didik di Sekolah Dasar Negeri 2 Ampenan - Nurhidayati; Hasbi, Nurmi; Hadziq, Muhammad Bayin; Lana, Indah Rosita; Miyamoto, Aida Agustina; Raykirana, Teerisha (Universitas Mataram, 2024)
The campus teaching program is a learning channel that provides students with the opportunity to study outside campus for one semester to practice their ability to solve complex problems by becoming partners with teachers to innovate in learning, development strategies and learning models that are creative, innovative and fun. The aim of this activity is a form of community service in improving literacy and numeracy skills. The method used in this activity is active collaboration between field supervisors, students and teachers at the school. This pursuit campus service activity was carried out at Ampenan 2 State Elementary School, Karang Pule Village, Sekarbela District, Mataram City. This service activity was carried out for four months. Some of the activities carried out to increase literacy and numeracy include library book fireplaces, numerical games on the kahood application, express Islamic boarding school activities during the fasting month, literacy and arithmetic assistance programs (calistung), helping to accompany teachers in teaching in class and so on. The student participants looked very enthusiastic about participating in campus teaching activities. Students felt great benefits from this activity. Students become more enthusiastic about studying and learning.